The Greening of US Free Trade Agreements : From NAFTA to the Present Day - Allen, Linda; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
This book provides an up-to-date critical analysis of the integration of environmental policies into US free trade agreements. The work focuses on the evolution of the design of environmental policies and analyzes their effectiveness. Starting with the North American Free Trade Agreement (NAFTA) leading to the Trans-Pacific Partnership (TPP), the book examines the history of policy integration. In doing so, it provides an overview of the major trade-related environmental policies and presents empirical research on their effectiveness, a discussion of the continued demand for policy integration in light of the effectiveness, and recommendations for addressing shortcomings. The main objective of the book is to inform the ongoing policy debate over integration of environmental policies into trade agreements. The current renegotiation of NAFTA provides an opportune time for undertaking this critical review of trade-related environmental policies. As our understanding and knowledge of the environmental policies associated with US trade agreements, in particular for NAFTA, has grown significantly over the past twenty-five years, this book provides a timely and critical update for this policy debate.Students and scholars of environmental law, trade and economics, and specifically US trade, environmental policy and law will find this book of great interest.
List of Tables -- Acknowledgments --Chapter 1 Introduction -- Chapter 2 Status Quo: Existing Environmental Policies -- Chapter 3 What Have We Learned -- Chapter 4 Future of Integration of Environmental Policies -- Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: Free trade -- Environmental aspects -- United States; Environmental policy -- United States; Environmental policy; Free trade -- Environmental aspects; LAW / Environmental; POLITICAL SCIENCE / Public Policy / Environmental Policy; Electronic books